2020
DOI: 10.1177/1474515120923785
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidity as a mediator of depression in adults with congenital heart disease: A population-based cohort study

Abstract: Background The population of adults with congenital heart disease (CHD) has increased dramatically with a high prevalence of acquired cardiac and non-cardiac comorbidities. However, the relationship among congenital heart disease, physical comorbidities, and psychological health in this population is not well studied. Aims The purpose of this study was to investigate (a) the association between adult congenital heart disease and the occurrence of depression and (b) whether physical comorbidities mediated the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 31 publications
1
6
1
Order By: Relevance
“…Previous studies comparing patients with CHD of all severities, including simple CHD, to controls found similar tendencies of patients with CHD having a higher prevalence of comorbidities compared with non-CHD controls. 15 , 24 , 25 In contrast to our findings, one study found that patients with CHD had a higher prevalence of neoplasms compared with controls in a 18- to 64-year-old cohort. 15 The difference may be due to their inclusion of severe CHD, as repeated radiation from chest X-rays, computed tomography scans, and procedures with catheterizations, often required in patients with severe CHD, is associated with a higher risk of neoplasms.…”
Section: Discussioncontrasting
confidence: 99%
“…Previous studies comparing patients with CHD of all severities, including simple CHD, to controls found similar tendencies of patients with CHD having a higher prevalence of comorbidities compared with non-CHD controls. 15 , 24 , 25 In contrast to our findings, one study found that patients with CHD had a higher prevalence of neoplasms compared with controls in a 18- to 64-year-old cohort. 15 The difference may be due to their inclusion of severe CHD, as repeated radiation from chest X-rays, computed tomography scans, and procedures with catheterizations, often required in patients with severe CHD, is associated with a higher risk of neoplasms.…”
Section: Discussioncontrasting
confidence: 99%
“… 15 In a recent population‐based study, adults with CHD had a significantly higher risk of depression than matched controls (adjusted hazard ratio, 1.43), with coronary artery disease and chronic obstructive pulmonary disease identified as significant comorbidities mediating the relationship between adult CHD and depression. 16 Depressive symptomatology was also independently impacted by the presence of HF in the current study. Therefore, the interaction between mood disorders and HF in adults with CHD may be multifactorial and involve similar mechanisms invoked in those with HF attributable to acquired heart disease.…”
Section: Discussionsupporting
confidence: 54%
“…Bracher et al studied comorbidities in a cohort of 1725 CHD cases from a single centre, reporting a 6.7% prevalence of either obstructive or restrictive lung disease, which was not further subclassified 16 . Yang et al carried out a case–control comparison of comorbidities in 2122 CHD patients and 8488 controls to determine mediators of any relationship between CHD and depression 6 . This study, alone among previous investigations, did find an increased relative risk of COPD in CHD cases (OR 2.08, 95% CI 1.75, 2.47), but the database utilised did not contain smoking data, so no adjustment for the main COPD risk factor could be made.…”
Section: Discussionmentioning
confidence: 99%
“…Such work has identified comorbid diseases that are more prevalent among adults with CHD, including various forms of cardiovascular disease 4 and chronic renal disease 5 , 6 . Although recent studies have suggested that the burden of chronic obstructive pulmonary disease (COPD) amongst adults with CHD may be greater than previously thought 6 , 7 , no sizeable prospective study with the capacity to adjust for important environmental factors predisposing to COPD has yet been conducted.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation